Investigating functional fitness of older adults in Korea in the period 2013–2018 - Jeoung, Bogja; Pyun, Do Young (Scientific reports, 2022)
The purpose of this study is two-fold: (a) to examine differences in the body compositions and the functional fitness tests across genders, age groups, and the test periods; and (b) to develop the functional fitness standards for older Korean adults. This is a cross-sectional study using data from the Korea Institute of Sport Science Fitness Standards. The data were derived from 155,256 old adults aged 65–90 who participated in the National Fitness Award Project from 2013 to 2018 in Korea. A series of t-test, ANOVA, and Cajori’s 5-grade method were used to analyze the data. The group comparison tests revealed significant differences in the body compositions and the fitness tests across genders ( p < 0.001 for all items), five age groups ( p < 0.001 for all items), and two test periods ( p < 0.001 for all items, except for sit-reach [ p = 0.138] in males and body mass index [ p = 0.258] and grip strength [ p = 0.130] in females). The study also proposed the guidelines for the functional fitness standards for this population. This study would provide useful information to practitioners to design more effective physical activity programs or interventions for people at-risk of declining health, thus improving health conditions of the older adults in Korea.